Natalizumab treatment alters the expression of T-cell trafficking marker LFA-1 α-chain (CD11a) in MS patients. (June 2014) - Jilek, Samantha; Mathias, Amandine; Canales, Mathieu; Lysandropoulos, Andreas; Pantaleo, Giuseppe; Schluep, Myriam; Du Pasquier, Renaud A
Objective: To determine the long-term effect of natalizumab (NTZ) treatment on the expression of integrins and chemokine receptors involved in the migration of T cells towards the central nervous system (CNS). Methods: We drew the blood of 23 patients just before starting NTZ therapy and every 12 months thereafter, for up to 48 months of treatment. We assessed the ex-vivo expression of phenotype markers (CCR7 and CD45RA), CNS-addressing integrins (CD11a, CD49d and CD29) and chemokine receptors (CXCR3 and CCR6) in CD4+ or CD8+ T-cell subsets by flow cytometry. Results: As compared to the pre-NTZ values, there was a marked increase in central memory (CCR7+/CD45RA-) CD4+ T cells and in effector memory (CCR7-/CD45RA-) CD8+ T cells at 12 and 24 months. In addition to an expected downregulation of both VLA-4 subunits (CD49d/CD29), we also found decreased T-cell expression of CXCR3 at 12 months, and of CD11a (LFA-1 αL subunit) at 12 months, but mostly at 24 months of NTZ treatment. Conclusion: Our data show a nadir of CD11a expression at 2 years of NTZ treatment, at the peak of incidence of progressive multifocal leukoencephalopathy (PML), indirectly suggesting that a lack of these molecules may play a role in the onset of PML in NTZ-treated patients.